If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -1) + 4x + 2 = 11 Reorder the terms: 5(-1 + 2x) + 4x + 2 = 11 (-1 * 5 + 2x * 5) + 4x + 2 = 11 (-5 + 10x) + 4x + 2 = 11 Reorder the terms: -5 + 2 + 10x + 4x = 11 Combine like terms: -5 + 2 = -3 -3 + 10x + 4x = 11 Combine like terms: 10x + 4x = 14x -3 + 14x = 11 Solving -3 + 14x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 14x = 11 + 3 Combine like terms: -3 + 3 = 0 0 + 14x = 11 + 3 14x = 11 + 3 Combine like terms: 11 + 3 = 14 14x = 14 Divide each side by '14'. x = 1 Simplifying x = 1
| x-126=35+8x | | -4=x+-7 | | Y=-16x^2+16x+5 | | Ax+5=bc-c | | x=9x+5-5 | | 6n+4=-2n | | (-32)+x=-18 | | 48kd=3.2k | | 6x-3+x-2=-5 | | X^2+45x-450=0 | | 4x-23/8= | | 12y+y(y-6)=4 | | 9x^2-18-2=0 | | 2(2+2n)=3(n+1) | | -110+3x=33-8x | | 5x+x=-42 | | -8=1/10z+3/10z | | 4x^6-24x^5+8x^4=0 | | 5n+3=2(n+2)+-3n | | y^2-10y-9=0 | | X+2x+3x=440 | | y=2x^2+16x+25 | | -q+9+7q=4q-9 | | 9x-4x+8=1x+20 | | -1/4+6=2/3x+28 | | 5x+2+2-2x=10 | | a=-10 | | y+7=.33333(x+2) | | X-(2x-5)=4x-(x+42) | | [-2x+22-3z]=[6x-2y+45] | | 4=3h-2 | | G-10=-9g+10 |